Vienna - Gavard, Charles, 1794-1871 (engraver):::Creator::::::::::::; Bénard (engraver):::Contributor::::::::::::; Dufour, Auguste-Henri, 1798-1865 (cartographer)::::::::::::::: (France; Jules Renouard Libraire; Paris)
Map of Vienna, Austria, from ca. 1830.